Uncovering the scholarly use of Twitter in the academia: Experiences in a British University - Ahmad Kharman Shah, Nordiana; Cox, Andrew M. (Malaysian Journal of Library and Information Science, 2017)
The potential of social media such as Twitter has been dubbed transformational. However, most of these effects have been studied in the political, social or technological sphere. Its impact on scholarship remains under-researched. The paper explores how academics use Twitter as part of their scholarly activities. A qualitative approach based on an interpretative methodology was adopted for the study, and data gathered through 28 semi-structured interviews with academic staff who regularly use Twitter for academic and non-academic purposes. The findings uncover the rich benefits that enthusiasts gain from use of Twitter as an information source for scholarly communication – in the context of creation, usage and sharing of scholarly information. This was manifested in academics’ information-seeking behaviour in with links to networking and collaboration as part of scientific practice.